(3SjGSI GdeQjOjfs - (3CHh GdMSjf CMeO Hf jMji Hf GdeDjOs
(3ChdgG (B:s
(3gPg eMWI GdEaJNGQ dCejQ GdeDefjf Ydi Hf CHj WGdH Qhi LGHQ Hf YHO Gddg Yf GdMSf GdHUQi bGd deG QLY CejQ GdeDefjf Ydi Hf CHj WGdH ef bJGd s
(3BNQgG (B:s
(3hcd QcYg aGJMI GdcJGH eQI hEPG LGA fUQ Gddg hGdaJM eQg hbd gh Gddg CMeO NeS hYTQjf eQg fMeO Gddg hUdhGJg Ydi QShdg SjOfG eMeO hBdg hSed JSdejkG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B3s
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdEeHQhRjGfG (B(265 d) s
Keywords: (3GdeLGejYs